People With Human Immunodeficiency Virus Receiving Suppressive Antiretroviral Therapy Show Typical Antibody Durability After Dual Coronavirus Disease 2019 Vaccination and Strong Third Dose Responses. (7th June 2022) - Lapointe, Hope R; Mwimanzi, Francis; Cheung, Peter K; Sang, Yurou; Yaseen, Fatima; Umviligihozo, Gisele; Kalikawe, Rebecca; Speckmaier, Sarah; Moran-Garcia, Nadia; Datwani, Sneha; Duncan, Maggie C; Agafitei, Olga; et al.
Abstract: Background: Longer-term humoral responses to 2-dose coronavirus disease 2019 (COVID-19) vaccines remain incompletely characterized in people living with human immunodeficiency virus (HIV) (PLWH), as do initial responses to a third dose. Methods: We measured antibodies against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein receptor-binding domain, angiotensin-converting enzyme 2 (ACE2) displacement, and viral neutralization against wild-type and Omicron strains up to 6 months after 2-dose vaccination, and 1 month after the third dose, in 99 PLWH receiving suppressive antiretroviral therapy and 152 controls. Results: Although humoral responses naturally decline after 2-dose vaccination, we found no evidence of lower antibody concentrations or faster rates of antibody decline in PLWH compared with controls after accounting for sociodemographic, health, and vaccine-related factors. We also found no evidence of poorer viral neutralization in PLWH after 2 doses, nor evidence that a low nadir CD4 + T-cell count compromised responses. Post–third-dose humoral responses substantially exceeded post–second-dose levels, though Omicron-specific responses were consistently weaker than responses against wild-type virus. Nevertheless, post–third-dose responses in PLWH were comparable to or higher than controls. An mRNA-1273 third dose was the strongest consistent correlate of higher post–third-dose responses. Conclusion: PLWH receiving suppressive antiretroviral therapy mount strong antibody responses after 2- and 3-dose COVID-19 vaccination. Results underscore the immune benefits of third doses in light of Omicron. Abstract : People living with human immunodeficiency virus with well-controlled viral loads on antiretroviral therapy and preserved CD4 + T-cell counts mount strong, functional antibody responses to 2- and 3-dose coronavirus disease 2019 vaccination, including to Omicron. Monitoring responses over time remains important.